Estudo químico e bioatividade de piranhea trifoliata (picrodendraceae). - Jeffreys , Manoel Feitosa (2011)
This work aimed to study the chemical extracts of Piranhea trifoliata (PICRODENDRACEAE) and its potential antimicrobial tests ahead, antioxidant, antimalarial and toxic. For the research was carried out on the four collections in the Volta Grande of Xingu (Altamira), PA, in epoch different. The collected material was dried at room temperature, crushed, pulverized and extracted with dichloromethane (DCM), the first and second sample, methanol (MeOH) and water (H2O), and three extractions performed by ultrasound in 20 minutes with each solvent. The plant material collected in the third and fourth were extracted with hexane solvent as its first. The DCM extracts of the leaves, leaf stems, twigs and stems showed signs of terpenes revealed when ceric sulfate, and the leaf extracts, the MeOH extracts of the leaves, twigs, bark, stem and the aqueous leaf, stem leaves, branch, and stems showed characteristics of phenolic compounds when revealed with ferric chloride. Phytochemical study of leaves of Piranhea trifoliata provided a triterpene: 28- hydroxy-Friedelin-3-one, identified by NMR of 1H and 13C and another substance characteristic of triterpenes was analyzed by 1H NMR. As for antimicrobial activity against Aeromonas hydrophila, showed activity MeOH and H2O extracts of the stems of the leaves (first collection), MeOH branches (1st gathering), MeOH and H2O of stems (2nd collection). The Minimum Inhibitory Concentration (MIC) the lowest value found was 2,5 mg/mL to H2O and MeOH extracts of the stems and leaf stalks (2nd collection) and the AcOET phase of the branches (1st collection), as the Minimum Bactericidal Concentration (CMB), the lowest value found was 5 mg/mL of AcOEt phase branches (1st collection). The antimalarial activity against P. falciparum showed activity extracts MeOH leaves, branches (1 st Collection), MeOH and H2O of stems and leaves (2nd collection), hexanes and MeOH leaves, bark and branches (3rd Collection) and MeOH from the leaves and branches (4th collection ). The antioxidant activity using the radical DPPH showed activity extracts MeOH and H2O of leaves and branches (1 st Collection), MeOH and H2O of leaves, stem and bark (2nd collection), MeOH leaves and bark (3rd Collection ), and branches of MeOH (4 th collection).